THU0359 Secukinumab demonstrates consistent safety over long-term exposure (up to 3 years) in patients with active ankylosing spondylitis: pooled analysis of three phase 3 trials. (15th June 2017) - Deodhar, A; Baraliakos, X; Marzo-Ortega, H; Sieper, J; Andersson, M; Porter, B; Fox, T
Abstract : Background: Safety data for secukinumab in the treatment of ankylosing spondylitis (AS) have been reported from three Phase 3 studies: MEASURE 1 (NCT01358175 ) 1, MEASURE 2 (NCT01649375 ) 1 and MEASURE 3 (NCT02008916 ). 2 Objectives: To report long-term (up to 3 years) pooled safety and tolerability data for secukinumab in AS (data cut-off: 25 June 2016). Methods: Overall, 371, 219 and 226 patients with active AS were randomised in MEASURE 1, MEASURE 2 and MEASURE 3, respectively. Study design, efficacy and safety results of these studies have been published earlier. 1, 2 Secukinumab doses differed in the studies and included intravenous 10 mg/kg or subcutaneous (75–300mg) multi-dose loading, followed by subcutaneous (s.c.) maintenance dosing (75, 150, or 300mg). Data collected up to the last patient performing the Wk 156 visit in MEASURE 1, the Wk 104 visit in MEASURE 2, and the Wk 52 visit in MEASURE 3 were pooled at the patient level. Exposure-adjusted incidence rates were calculated to account for differences in treatment exposure and analyses included all patients who received ≥1 dose of secukinumab 150 or 300mg. Results: A total of 510 patients were included in the analysis (968.9 patient-years of exposure). The exposure-adjusted AE and SAE rates with secukinumab across the entire safety period were 159.2 and 5.4 per 100 patient-years, respectively. Nasopharyngitis, diarrhoea and headache were the most frequently reported AEs. The incidences of Candida infections, serious infections, inflammatory bowel disease, major adverse cardiac events, neutropenia and uveitis were low and consistent with previous reports over shorter exposure periods 1 (Table). No cases of suicidal ideation or depression were reported. Conclusions: This longer-term safety assessment of secukinumab in the treatment of AS was consistent with previous reports and did not identify any new safety signals. References: Baeten D, et al. N Engl J Med 2015;373:2534–48. Kivitz A, et al. XIX PANLAR 2016, Panamá City, Panama. Poster No. P-081. Disclosure of Interest: A. Deodhar Grant/research support from: AbbVie, Amgen, Eli Lilly, GSK, Janssen, Novartis, Pfizer, and UCB; advisory board member: Eli Lilly, Janssen, Novartis, Pfizer, and UCB., X. Baraliakos Grant/research support from: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, and Werfen, Consultant for: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, and Werfen, Speakers bureau: AbbVie, BMS, Celgene, Chugai, Merck, Novartis, Pfizer, UCB, and Werfen, H. Marzo-Ortega Grant/research support from: Janssen and Pfizer, Consultant for: AbbVie, Celgene, Janssen, Novartis and UCB, Speakers bureau: Abbvie, Celgene, Janssen and UCB, J. Sieper Grant/research support from: for AbbVie, Boehringer Ingelheim, Janssen, Novartis, Merck, Lilly, Pfizer, and UCB, Consultant for: for AbbVie, Boehringer Ingelheim, Janssen, Novartis, Merck, Lilly, Pfizer, and UCB, M. Andersson Employee of: Novartis, B. Porter Shareholder of: Novartis, Employee of: Novartis, T. Fox Shareholder of: Novartis, Employee of: Novartis